2011
DOI: 10.1186/1471-2458-11-115
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of air pollution and surrogate markers of endothelial dysfunction in a population-based sample of children

Abstract: BackgroundThis study aimed to assess the relationship of air pollution and plasma surrogate markers of endothelial dysfunction in the pediatric age group.MethodsThis cross-sectional study was conducted in 2009-2010 among 125 participants aged 10-18 years. They were randomly selected from different areas of Isfahan city, the second large and air-polluted city in Iran. The association of air pollutants' levels with serum thrombomodulin (TM) and tissue factor (TF) was determined after adjustment for age, gender, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
19
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 47 publications
5
19
0
1
Order By: Relevance
“…A cross-sectional study conducted among young participants aged 10-18 years, randomly selected from different urban areas of Isfahan city, the second largest and air-polluted city in Iran, showed a higher correlation between fine particulate matter and platelet tissue factor expression, a coagulation factor associated with atherosclerotic cardiovascular disease. This finding is consistent with various experimental studies that showed exposure to PM increases platelet tissue factor expression in atherosclerotic lesions [Poursafa et al, 2011]. Despite accumulating data indicating that particulate matter exposure contributes to the progression of atherosclerosis in animal models and in humans, the strength of associations between PM and atherosclerosis in humans is still being debated, and the strength and relative importance of the mechanisms in contributing to cardiovascular morbidity and mortality is still to be ascertained.…”
Section: Vascular Changes and Alterations In Blood-borne Factors Indusupporting
confidence: 78%
“…A cross-sectional study conducted among young participants aged 10-18 years, randomly selected from different urban areas of Isfahan city, the second largest and air-polluted city in Iran, showed a higher correlation between fine particulate matter and platelet tissue factor expression, a coagulation factor associated with atherosclerotic cardiovascular disease. This finding is consistent with various experimental studies that showed exposure to PM increases platelet tissue factor expression in atherosclerotic lesions [Poursafa et al, 2011]. Despite accumulating data indicating that particulate matter exposure contributes to the progression of atherosclerosis in animal models and in humans, the strength of associations between PM and atherosclerosis in humans is still being debated, and the strength and relative importance of the mechanisms in contributing to cardiovascular morbidity and mortality is still to be ascertained.…”
Section: Vascular Changes and Alterations In Blood-borne Factors Indusupporting
confidence: 78%
“…The association of air pollution and inflammation/oxidative stress has been demonstrated (Huang et al, 2003;Ruckerl et al 2006;Chuang et al, 2007), even among healthy children (Kelishadi et al, 2009) who might have the early stages of atherosclerosis. Such association is also confirmed for air pollutants, notably particulate matters and surrogate markers of endothelial dysfunction and markers of vascular injury (Poursafa et al, 2011). The effects of air pollution on inflammation, coagulation, oxidative stress and endothelial dysfunction from early life confirm the necessity of implications of these findings in relation to public health and regulatory policies for primordial/primary prevention and control of adult chronic diseases from childhood.…”
Section: Environmental Factors Lifestyle Behaviors and Chronic Diseasessupporting
confidence: 48%
“…In order to correctly reference this scholarly work, feel free to copy and paste the following: Parinaz Poursafa and Roya Kelishadi (2011). Air Pollution and Primordial Prevention of Chronic NonCommunicable Diseases, Air Pollution -New Developments, Prof. Anca Moldoveanu (Ed.…”
Section: Air Pollution -New Developmentsmentioning
confidence: 99%
“…Além dos efeitos da poluição atmosférica sobre as doenças respiratórias e imunológicas, e também sobre os estágios iniciais da aterosclerose 4,31 , sugeridos anteriormente, os achados do nosso estudo propõe uma associação entre poluentes do ar e atividade da medula óssea. Ao considerar os efeitos carcinogênicos dos poluentes atmosféricos para as crianças 32 , nossos achados podem alertar para efeitos mais preocupantes da poluição atmosférica para a saúde das crianças.…”
Section: Discussionunclassified